A Research and Critical Review of Iqbal's Poem Khizr-e- Rah in the Context of Neo-historicism - Javed, Tariq; Kousar, Robina (sourcecoder, 2024)
This research critically examines Allama Iqbal’s poem Khizr-e-Rah through the lens of neo-historicism, which explores the hidden meanings within historical and socio-political contexts. Delivered in Lahore on April 16, 1922, the poem presents a dialogue between Iqbal and Khizar, reflecting on global politics and the state of the Muslim world. By analyzing the political, social, and cultural conditions of its time, this study investigates the circumstances that influenced Iqbal’s thoughts and poetic expression. The research addresses key questions: What political and historical events shaped Iqbal’s worldview, particularly in India, Iran, and the Ottoman Empire? How did cultural trends and geographical changes impact the Muslim world? What challenges did colonialism and Western influence pose to the East? Iqbal’s poetry encapsulates these concerns, offering a critique of prevailing conditions and a vision for revival. Employing a mixed-methods approach, this study combines literary analysis with historical research to uncover the deeper significance of Khizr-e-Rah. The findings suggest that the poem symbolically represents Iqbal’s philosophy of khudi (selfhood) and serves as a call to action for the Muslim Ummah. It emphasizes that intellectual awakening, self-reliance, and relentless struggle are essential for the resurgence of Muslim identity and power. This research concludes that Khizr-e-Rah is not merely a poetic expression but a historical and ideological commentary, urging Muslim youth to embrace knowledge, hard work, and perseverance. By revisiting this work through a neo-historicist perspective, the study highlights Iqbal’s relevance in contemporary socio-political discourse and his enduring influence on Muslim thought.